Making the Nation's Investment in Student Access and Success Part I: Refocusing the HEA Reauthorization to Reflect the Priorities of Higher Education Policy Analysts and Researchers - Hansen, W. Lee; Stampen, Jacob (My University, 2004)
In this two-part study, the authors asked 203 of the nation's most active higher education researchers and policy analysts to respond to 86 current ideas for expanding and increasing student success. According to the respondents, the highest priorities for improving postsecondary access and success are 1) improving academic preparation and 2) providing more resources for student need-based financial aid grants. The priorities of the responding groups of analysts and researchers proved to be surprisingly similar; however, the authors found that it is difficult to link these most strongly supported options to a new research-based model (the "Pathways Model") with enough clarity to predict what actions will yield the greatest benefits for students. The Pathways Model provides the most complete analysis of factors impacting college student access and academic success and shows that neither socioeconomic status nor ethnic background are insurmountable barriers. The authors found that more research is needed to determine what solutions will work best for increasing college student access and success. Still, matches between what analysts think and what research supports are clear enough to indicate that policies and programs based on research are likely to provide many more benefits to future students than those based mainly on political considerations. The authors recommend that four actions be taken simultaneously in order to substantially improve the educational system's effectiveness: 1) avoid adopting wasteful and costly policies that are unsupported by research and can therefore do little to eliminate barriers to better education; 2) focus K-12 instruction on improving learning overall and especially help at-risk students overcome learning obstacles they face as individuals; 3) make college more affordable for low income students; and 4) create better mechanisms for informing the collective efforts of everyone involved in improving learning.
Keywords: The Pathways Model; Finance and Economics; Accountability, Autonomy, and Politics; Access, Persistence, and Success